Engineering of GO/MWCNT/RuO2 ternary aerogel for high-performance supercapacitor. (1st December 2022) - Karimi, Fatemeh; Korkmaz, Satiye; Karaman, Ceren; Karaman, Onur; Afşin Kariper, İ.
Graphical abstract: Highlights: GO/MWCNT/RuO2 ternary aerogel was synhesized via facile production pathway. The high specific capacitance value was attained as 329.3F.g −1 even at 10.0 A.g −1 . The capacitance retention of was reached up to 94.38% for the 5, 000th CV cycle. The energy density of 37.96 W.h.kg −1 was attained at a power density of 8.33 kW.kg −1 . Abstract: It is of great importance to fabricate high-performance electrode materials via a facile fabrication pathway to be utilized in energy storage systems, specifically in supercapacitors. Herein, ruthenium(IV) oxide (RuO2 ) was decorated onto the nanocomposite of graphene oxide (GO) and functionalized multi-walled carbon nanotubes (MWCNT) via straight forward production pathway for the first time, and the resultant nanostructure was then characterized physicochemically via x-ray diffraction spectroscopy (XRD), Fourier transform infrared spectroscopy (FTIR), field-emission scanning electron microscope (FESEM), and energy dispersive X-ray analysis (EDX). The fabricated nanostructure was employed as the electrode material to develop a high-energy symmetrical supercapacitor cell. The electrochemical performance of the as-assembled supercapacitor was assessed by cyclic voltammetry (CV), and galvanostatic charge–discharge (GCD) techniques. The highest specific capacitance was achieved as 514.9F.g −1 at a current density of 0.5 A.g −1 . Moreover, even at a high current density of 10.0 A.g −1, the specific capacitance value was computed still as high as 329.3F.g −1 . The superior capacitance retention feature (94.38 % at the end of 5, 000th consecutive CV cycles) revealed the outstanding electrochemical activity of the electrode material. The attained energy density of 37.96 W.h.kg −1 (at a power density of 8.33 kW.kg −1 ) implied the potential application of the proposed supercapacitor cells as a high-energy system.